PELATIHAN MEMINIMALISIR PEMBERITAAN HOAX MEDIA SOSIAL DAN PENERAPAN INTERNET SEHAT - Munaldi Munaldi; Ferry Agus Sianipar; Muhammad Cordiaz (Jurnal Pengabdian Masyarakat Nasional, 2023)
At this time, the progress of science and technology is very rapid, making it easier for people to access everything, one of which is the information needed. Along with its development, technological advances not only have a positive impact but also have a negative impact. In accessing information at this time, the delivery of information will be very easy and fast. Where someone very easily produces information and shares it via social media such as Facebook, Twitter, Instagram, Google, Youtube or handheld messages such as WhatsApp, LINE, BBM (Blackberry Messenger) and so on which cannot be filtered properly. Information that has been read can affect emotions, feelings, thoughts and even actions of both individuals and groups. It is very unfortunate if social media is used to obtain and provide inaccurate information, especially to the point of making social media a tool for spreading fake news (hoaxes) using very provocative titles to direct readers to negative public opinion. A fake report is different from, for example, a magic show, in that it is fake news, the listener/audience is not aware that they are being lied to, whereas in a magic show, the audience actually expects to be deceived. Fake news (hoaxes) need to get serious attention at this time because hoaxes themselves are "an act of communication carried out by an individual or group in the form of provocation, incitement, or insult to other individuals or groups to make things disorderly and trigger fights, debates and divisions for a person, group or nation and state. This is done by irresponsible people to benefit both psychologically and financially.